Design and analysis of high performance and low power matrix filling for DNA sequence allignment accelerator using ASIC design flow / Nurul Farhana Abd Razak - Abd Razak, Nurul Farhana (2010)
Efficient sequence alignment is one of the most important and challenging activities in bioinformatics. Many algorithms have been proposed to perform and accelerate sequence alignment activities. Among them Smith-Waterman (S-W) is the most sensitive (accurate) algorithm. This paper presents a novel approach and analysis of High Performance and Low Power Matrix Filling for DNA Sequence Alignment Accelerator by using ASIC design flow. The objective of this paper is to improve the performance of the DNA sequence alignment and to optimize power reduction of the existing technique by using Smith Waterman (SW) algorithm. The scope of study is by using the matrix filling method which is in parallel implementation of the SmithWaterman algorithm. This method provides more efficient speedup compared to the traditional sequential implementation but at the same time maintaining the level of sensitivity. The methodologies of this paper are using FPGA and Synopsis. This technique is used to implement the massive parallelism. The design was developed in Verilog HDL coding and synthesized by using LINUX tools. Matrix Cells with a design area 8808.307mm2 at 40ns clock period is the best design. Thus the power required at this clock period also smaller; dynamic power 111.1415uW and leakage power 212.9538Nw. This is a large improvement over existing designs and improves data throughput by using a ASIC design flow.